Transient Fault Tolerance in Mobile Agent Based Computing - Saha, Goutam Kumar (INFOCOMP Journal of Computer Science, 2005)
Agent technology is emerging as a new paradigm in the areas of distributed and mobile computing. Agent is a computational entity capable of relocating code, data and execution- state to another host. Mobile agents' code often experience transient faults resulting in a partial or complete loss during execution at a host machine. Protocol for fault – tolerant agent prevents a partial or complete loss of a mobile agent at a host. This article describes how to detect and recover random transient bit-errors at an agent before starting its execution at a host after its arrival at a host, in order to maintain availability of an agent by comparing an agent's states by using time and space redundancy. In this proposed self-repair approach, a software fix for fault – tolerance exists along with an agent. This generalized scheme is useful for recovering any kind of distributed agents against hardware transient faults (at a host). This paper presents a fault-tolerance mechanism for mobile agents that attempts to detect and correct any bit errors that may occur at a host after agents' mobility on a Web Agent-based Service Providing (WASP) platform. Though in modern distributed systems, the communication stack handles any bit errors and error correction is used on multiple layers (for example, in transport layer), the proposed approach is intended to be a supplement one to the conventional error detecting and correcting codes.